2014
DOI: 10.1007/s12253-014-9796-4
|View full text |Cite
|
Sign up to set email alerts
|

The Guidance of Intraoperative Frozen Section For Staging Surgery in Endometrial Carcinoma

Abstract: The objective of this study was to evaluate the reliability of an intraoperative frozen section during the endometrial carcinoma staging surgery procedure. The paraffin section reports of 291 cases with endometrial carcinoma were compared with intraoperative frozen section reports, which were diagnosed in the Pathology Department of Cukurova University, Medical Faculty between June 2006 and December 2012. The reports were reviewed for diagnostic accuracy of the frozen section in terms of histological subtype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…One of the 5 studies used IGE 22 and 4 studies used IFS. 14,24,41,43 This number is too small to perform a meaningful meta-analysis. However, considering the 4 studies using IFS, pooled sensitivity, specificity, LR+, and LRj were 83% (95% CI, 73%Y90%), 97% (95% CI, 95%Y99%), 30.2 (95% CI, 15.6Y58.7), and 0.17 (95% CI, 0.11Y0.29), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the 5 studies used IGE 22 and 4 studies used IFS. 14,24,41,43 This number is too small to perform a meaningful meta-analysis. However, considering the 4 studies using IFS, pooled sensitivity, specificity, LR+, and LRj were 83% (95% CI, 73%Y90%), 97% (95% CI, 95%Y99%), 30.2 (95% CI, 15.6Y58.7), and 0.17 (95% CI, 0.11Y0.29), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5 studies specifically described that high-risk patients (serous carcinoma, clear cells, carcinosarcoma, or undifferentiated carcinoma) were excluded, one using IGE 22 and 4 using IFS. 14,24,41,43 For the domain ''Index test'', in 26 of the 35 studies, index test was adequately described in 11 of 14 for studies using IGE and in 15 of 21 for studies using IFS. 9Y12,15Y23, 25Y30,32,33,35Y43 For the domain ''Reference standard'', in all studies, reference standard was final histopathology, which is correct, but only one described in detail how this was done.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the IOA had a 76% concordance rate with the final pathology report, with the best overall predictor being myometrial invasion. Studies have found myometrial invasion to be a good predictor of node metastasis, with a sensitivity as high as 86% [ 7 ]. Our overall accuracy for myometrial invasion was 82%.…”
Section: Discussionmentioning
confidence: 99%
“…If the intraoperative assessment (IOA) shows high-risk factors, complete surgical staging is recommended [ 6 ]. That is, as pelvic and paraaortic lymphadenectomy procedures increase morbidity and the surgical time, they are not performed routinely [ 7 ]. Furthermore, the final pathology report can differ from intraoperative findings, and IOAs could lead to unnecessary surgeries in women with low-risk disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%